2015
DOI: 10.1007/s11771-015-2857-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on thermal characteristics of nanofluid with graphene and multi-wall carbon nanotubes

Abstract: High-thermal conductivity enhancement of nanofluid is one of the promising topics of the nanoscience research field. This work reports the experimental study on the preparation of graphene (GN) and multi-walled carbon nanotubes (MWCNTs) based nanofluids with the assistance of sodium dodecyl benzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS) surfactants, and their thermal behaviors. The present work suggests not a solution, but a solution approach and deduces a new conclusion by trying to resolve the agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 37 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…This indicates that the addition of surfactants increases the absolute zeta potential value of Water-GNP nanofluid, which corresponds with a lower tendency to flocculate. Further, SDBS-based nanofluid has the highest stability, followed by SDS-based nanofluid, which agrees with the study by [26,27]. In order to validate the zeta potential result, UV-Vis analysis was performed on the surfactantdispersed nanofluids due to the presence of little sediments.…”
Section: Solid State Phenomena Vol 355supporting
confidence: 84%
“…This indicates that the addition of surfactants increases the absolute zeta potential value of Water-GNP nanofluid, which corresponds with a lower tendency to flocculate. Further, SDBS-based nanofluid has the highest stability, followed by SDS-based nanofluid, which agrees with the study by [26,27]. In order to validate the zeta potential result, UV-Vis analysis was performed on the surfactantdispersed nanofluids due to the presence of little sediments.…”
Section: Solid State Phenomena Vol 355supporting
confidence: 84%
“…Yarmand et al [147,161] increased the stability of nanofluids by introducing the hydroxyl and carboxyl function groups toward the GNP surface. With the same purpose, Mehrali et al [80] prepared NDG by a hydrothermal process with GO as a raw material [205] SPC + UV-Vis N/A Polymers P19 and P20 [206] ZPT N/A Changing pH [104] SPC + TC~ 7 days N/A [105] TC~ 150 days (5 months) N/A [117] SPC + UV-Vis~ 7 days N/A [118] SPC, UV-Vis, ZPT~ 60 days N/A [115] SPC N/A N/A [114] SPC, UV-Vis, ZPT~ 180 days (6 months) Triton X-100 [113] SPC N/A N/A [112] SPC 24 h N/A [3] SPC, UV-Vis, ZPT 600 h N/A [107] UV-Vis 1 week PVA [123] SPC 7 days N/A [122] ZPT + SPC N/A Modifying pH and tannic acid [121] SPC 2 months Modifying pH [124] SPC 4 days SDBS [129] SPC + UV-Vis 256 h N/A [131] ZPT, PSD, SPC~ 1 month Sodium carboxymethyl celluloses [132] DLS + TC > 2 months (0.005%), few days (> 0.005%)…”
Section: Stability Enhancement Proceduresmentioning
confidence: 99%
“…It also additionally depends on the polarity of the base fluid, such as, in the research work of Al-Waeli et al (2019), CTAB was found to provide the maximum stability to the nanofluid, which was used by the authors to study the efficiency of the photovoltaic-thermal systems. SDS, on the other hand, has also been used extensively for stabilizing graphene/water-based nanofluid for welding, turning, and grinding processes (Haque et al, 2015;Seong et al, 2018;Zhai et al, 2019) and has been found to be quite effective. Selvam et al (2017) studied the stability mechanism and performance of sodium deoxycholate on graphene-based nanofluids and concluded that not only the mixture was stable, but the magnitude of the coefficient of thermal convection surpassed 100%.…”
Section: Surfactants Used In Stabilizing Organic Nanofluidsmentioning
confidence: 99%